Patent Value Analysis Based on the EPTV Model Investigation of Building Energy-Saving Industry - Wang, Fu-Xin; Zhang, Ben; Qiu, Hong-Hua; Yang, Wei (Journal of Strategic Innovation and Sustainability, 2020)
Building energy efficiency technology is hoped to play an important role in climate change. Taking the building energy-saving industry as the research sample, this paper aims to investigate the patent competition situation with an intelligence analysis of EPTV model. This study explored the patent competition situation among the major applicants according to the high-value patent layouts. The results of intelligence analysis indicate that the EPTV model provides a panoramic overview of patent value for the building energy-saving industry, which also provides a new perspective for patent competition situation investigation and some implication suggestions for the industry development.